An exploration study on blended learning experiences in a public higher institution in Malaysia / Johan @ Eddy Luaran ... [et al.] - Luaran, Johan @ Eddy; Alias, Nor Aziah; Mohd Yusof, Mohammad Mubarrak (UiTM Press, 2017)
The advancement in information communication technology (ICT) has changed how people communicate with each other in both society and the business world. In higher education (HE), it has changed how stakeholders such as students and academics gain access to information. Academics need not carry a pile of books to lecture or print out dozens of handouts; research students no longer need to attend the library to renew books or to find a journal article. Instead, the Virtual Learning Environment (VLE), digital library, online journal articles and a variety of educational ICT are pervasive. Technological innovations impact on the learning and teaching experience in higher educational institutions (HEIs). Many universities have spent much effort and resources in attempting to respond to such changes related to the digital culture and move to blended learning approach. Blended learning, involves the combination of two fields of concern: technology and education. However, current literature shows less consideration on the potential disciplinary gap in the blended learning experience, as a result there is a paucity of evidence from institutional investigations. This study aimed to explore, analyse and compare the blended learning experience in higher education. The research is reflected in 3 questions: (1) What are the current blended learning experiences in the higher educational institutions in Malaysia? (2) How does the blended learning experience vary in different disciplines (social science-based academics and science-based academics)? (3) What are the reflections on the comparative experiences in (1) and (2)? In addition, the research offers a contribution to knowledge that leads to the establishment of an underlying blended learning model in the later stage. The research aims for a notable shift from the conventional technological framework towards an insight into the blended learning principles underpinned by educational theory.